Comparative analysis of methane conversion: pyrolysis, dry and steam thermal plasma reforming - Essiptchouk, Alexei [UNESP]; Miranda, Felipe; Petraconi, Gilberto (IOP Publishing, 2024)
Methane reforming is gaining attention because of its potential to be converted into energy-dense fuels or high-value chemicals. In addition to the production of syngas (H2+CO), the utilization of CO2 can help reduce greenhouse gases. Water steam is typically used to increase the output of H2. This study evaluated the potential of thermal plasma technology to produce clean hydrogen, carbon monoxide, and carbon black from methane by applying a thermodynamic equilibrium model. A comparative analysis of three cases of methane processing (pyrolysis, dry reforming, and steam reforming) is presented to provide a comprehensive understanding of the potential of thermal plasma technology for methane conversion.
Keywords: clean hydrogen; energy conversion efficiency; reforming of methane; thermal plasma; thermodynamic equilibrium